Analysis of Interest in Learning Biology Maple in Class X Students of Class Cross Interest At Sman 1 Bilah Hilir - Murni Murni; Novi Fitriandika Sari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine students' interest in learning biology in class X Clump Lintas Interest at SMAN 1 Bilah Hilir. Interest is a sense of liking and a sense of attachment to a thing or activity, without anyone telling. Cross Interest Clusters are subjects that can be taken by students outside the chosen Specialization Subject Group but are still in other Specialization Groups. The research method used is descriptive quantitative research. Data collection in this study was carried out by means of: observation, questionnaires and interviews. Calculation of data analysis using a Likert scale with the provisions of 4 = strongly agree, 3 = agree, 2 = disagree, 1 = strongly disagree). The results of this study indicate that students' interest in learning biology in the cross-interest cluster of class X students at SMAN 1 Bilah Hilir has an interest in learning biology with an average percentage of 76.05% including in the high category. Interest in learning biology consists of 74.13% (high category), 74.29% interest (high category), 76.90% interest (high category), and 75.89% involvement (high category).